2021
DOI: 10.3390/polym13162759
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Nanocrystals Reinforced Zein/Catechin/β-Cyclodextrin Inclusion Complex Nanoparticles Nanocomposite Film for Active Food Packaging

Abstract: In this study, following the green, environmentally friendly and sustainable development strategy, cellulose nanocrystals (CNCs) were prepared through a solvent-free esterification reaction between microcrystalline cellulose and maleic anhydride, combined with subsequent ultrasonic treatment, and maleic-anhydride-modified CNC-reinforced zein/catechin/β-cyclodextrin inclusion complex nanoparticles nanocomposite films were prepared by a facile solution casting. The amount of CNCs in the film matrix was 0–8 wt%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 54 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…These observations suggested that the BITC−α−CD dispersed in the composite film solution in an even manner, indicating the favorable compatibility between BITC−α−CD and CS film−forming solution. Moreover, no large agglomerations in the microscopic surface of CS−BITC−α−CD composite film suggested that BITC−α−CD can be well dispersed in the CS film matrix due to intermolecular forces, which might be beneficial to improve the film strength [ 47 ]. The previous study reported that the uniform distribution of cellulose nanocrystals in the CS film effectively enhanced the physical and mechanical properties of the CS film matrix [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggested that the BITC−α−CD dispersed in the composite film solution in an even manner, indicating the favorable compatibility between BITC−α−CD and CS film−forming solution. Moreover, no large agglomerations in the microscopic surface of CS−BITC−α−CD composite film suggested that BITC−α−CD can be well dispersed in the CS film matrix due to intermolecular forces, which might be beneficial to improve the film strength [ 47 ]. The previous study reported that the uniform distribution of cellulose nanocrystals in the CS film effectively enhanced the physical and mechanical properties of the CS film matrix [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…After the chitin nanofibers were added, the film formed a dense microstructural network, which was beneficial to enhancing the water vapor barrier capacity. Previous studies have also found that cellulose nanofibers can decrease the WVP value of polymer films ( Huq et al, 2012 , Jiang et al, 2021a ). As the essential oil content was increased, the WVP value of chitosan-based films significantly decreased (p < 0.05), suggesting that the addition of hydrophobic substances can reduce the WVP of film.…”
Section: Resultsmentioning
confidence: 76%
“…Addition of the chitin nanofibers did not significantly improve the antioxidant capacity of the chitosan-based film (p greater than 0.05), which was due to the lack of antioxidant activity of chitin. Our previous study also showed that cellulose nanocrystals did not improve the antioxidant activity of zein films ( Jiang et al, 2021a ). With the incorporation of REO, the scavenging ratios of DPPH and ABTS of the films were notably enhanced (p < 0.05).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Also, nanotechnology was used for sustainable food packaging. It included blending curcumin with sodium caseinate‐mixed zein nanoparticles (L. Wang et al., 2019), adding gelatin‐kappa‐carrageenan with thymol and zein nanoparticles (Maroufi et al., 2021), zein films added with chitosan nanoparticles and pomegranate‐peel extract (Cui et al., 2020), plasma‐treated zein–catechin–β${{\beta}}$‐cyclodextrin nanocomposite films incorporated with cellulose nanocrystals (L. Jiang et al., 2021), and cellulose nanofibrils mixed with zein nanoparticles as nanocomposites (Q. Li et al., 2020).…”
Section: Protein‐based Polymers For Food Packagingmentioning
confidence: 99%